Magnetic Resonance Sialography Findings of Submandibular Ducts Imaging. (25th July 2013) - Karaca Erdoğan, Nezahat; Altay, Canan; Özenler, Nesibe; Bozkurt, Tuğba; Uluç, Engin; Dirim Mete, Berna; Özdemir, İsmail
Abstract : Purpose . We aimed to assess the problem solving capability of magnetic resonance sialography (MR sialography), a noninvasive method for imaging submandibular gland ducts and determining duct-related pathologies, by comparing diseased and healthy cases. Materials and Methods . We conducted radiological assessment on a total of 60 submandibular glands (mean age 44.7) in 20 cases and 10 volunteers. MR sialography examinations were conducted with single-shot fast spin-echo sequence by using a surface coil placed on the submandibular gland. Each gland was evaluated in terms of the length, width and stricture of the main duct, as well as the difference between the intraparenchymal duct width, and the main duct width. Statistical analysis was performed. Results . In the MR sialography the primary duct mean length was determined as 51 mm (40–57 mm) in all submandibular glands. On the MR sialography imaging, the visualization ratio of the ductal system of submandibular gland was evaluated in the cases and volunteers. Conclusion . MR sialography is an effective and a noninvasive method in imaging submandibular gland ducts, demonstrating the presence, location and degree of stricture/dilatation, and elucidating the disease etiology.